Recordings of Nisgha language field studies - Azak, Bertha; Belvin, Robert S.; Grandison, Pauline; Haizimsque, Sam; Haizimsque, Sarah; Robinson, Rosie; Williams, Verna (1989)
Linguistic field recordings in Vancover, British Columbia in August and September 1989, and in New Aiyansh, British Columbia in August 1990. Nisgha language elicitations, Vocabularies, and grammar; narratives about the Nisgha and Gitxsan, and the flooding of Old Aiyansh; free translations of Psalm 23 and the Lord's Prayer into Nisgha; brief Christian hymn sung in Nisgha.